On some new species of Canuelloida Khodami, Vaun MacArthur, Blanco-Bercial & Martinez Arbizu, 2017 (Crustacea: Copepoda) from a shallow coastal lagoon in north-western Mexico - Gómez, Samuel; Yáñez-Rivera, Beatriz; García-Vázquez, Leonardo; Armenteros, Maickel (Zootaxa, 2024)
Several benthic copepods were found in sediment samples taken during a short-term project on the diversity and distribution patterns of macro- and meiofauna in Ohuira Bay (northern Sinaloa state, north-western Mexico). The material turned out to belong to two new species, Scottolana tama sp. nov. and Canuellina pacifica sp. nov., and to Longipedia corteziensis Gómez, 2001 previously known from a shallow coastal lagoon not far from Ohuira Bay. New groupings of the species of Scottolana Huys, 2009 and Canuellina Gurney, 1927 are proposed and the description of the new species is provided. Additionally, the distribution patterns of S. tama sp. nov., C. pacifica sp. nov., and L. corteziensis in Ohuira Bay are discussed.